2018
DOI: 10.1073/pnas.1714597115
|View full text |Cite
|
Sign up to set email alerts
|

High fire-derived nitrogen deposition on central African forests

Abstract: Atmospheric nitrogen (N) deposition is an important determinant of N availability for natural ecosystems worldwide. Increased anthropogenic N deposition shifts the stoichiometric equilibrium of ecosystems, with direct and indirect impacts on ecosystem functioning and biogeochemical cycles. Current simulation data suggest that remote tropical forests still receive low atmospheric N deposition due to a lack of proximate industry, low rates of fossil fuel combustion, and absence of intensive agriculture. We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 51 publications
3
60
0
Order By: Relevance
“…Interestingly, the proportion of relative abundance from condensed aromatics was higher in the forested area DOM compared to DOM from the deforested catchments (Figure a), potentially indicating the input of combustion byproducts via atmospheric deposition (Stubbins, Silva, Dittmar, & Van Stan, ). Indeed, recent research has shown that mixed lowland forests of the Congo capture high amounts of atmospheric aerosols relative to open field sites due to their large foliar surface areas upon which dry deposition can occur (Bauters et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the proportion of relative abundance from condensed aromatics was higher in the forested area DOM compared to DOM from the deforested catchments (Figure a), potentially indicating the input of combustion byproducts via atmospheric deposition (Stubbins, Silva, Dittmar, & Van Stan, ). Indeed, recent research has shown that mixed lowland forests of the Congo capture high amounts of atmospheric aerosols relative to open field sites due to their large foliar surface areas upon which dry deposition can occur (Bauters et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of high N deposition rates (Bauters et al. ) and the downregulation of symbiotic BNF (Bauters et al. ) suggests that lowland tropical forests in the Congo Basin are indeed N rich.…”
Section: Discussionmentioning
confidence: 99%
“…A final important assumption of the N paradox is that there is low N deposition in most remote sites. Again here, recent studies have shown that DON deposition can contribute largely to total N deposition although it has been ignored in most studies and that the atmospheric N deposition in central Africa is much higher than expected from simulations (Mace et al 2003, Cape et al 2011, Cornell 2011, Bauters et al 2018. The few studies that include DON deposition in N balances usually come up with N inputs that could outbalance reported N export ranges (Appendix S1: Table S2).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We also acknowledge N deposition may be underestimated due to the Tdep model's limited treatment of dry organic N, which can be particularly high in regions exposed to savanna fires where N‐rich, fire‐derived aerosols can be trapped by the forest canopy and enter the system via throughfall (Bauters et al. ). However, previous research in pine stands at Benning reported a flux of throughfall organic N of only 0.28 kg N·ha −1 ·yr −1 (Bhat et al.…”
Section: Discussionmentioning
confidence: 99%